2018
DOI: 10.5152/tpd.2018.4824
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Blebharitis: Phthiriasis Palpebrarum

Abstract: A six-year-old male patient was admitted to our hospital due to itching and scalding crusts that persisted 10-15 days in both eyes. Upon biomicroscopic examination, 5-6 semi-translucent, yellowish brown living lice attached to the upper eyelashes and a large number of eggs were observed. Following application of pilocarpine hydrochloride (Pilomann 2%, Bausch-Lomb) and topical proparacaine hydrochloride (Alcaine 0.5%, Alcon), the paralyzed parasites and eggs were manually removed by pulling with forceps. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The eyelid needs careful examination with good lighting, possibly requiring a slit lamp. Case reports have suggested various treatments, including tea‐tree oil, physostigmine, pilocarpine and fluorescein ophthalmic drops; these seem to be used for occlusive purposes with no obvious pediculicidal properties 9,18,28,29 . Cryotherapy, argon lasers or botox have been used in difficult cases to structurally damage the lice and facilitate removal 18–19,29 .…”
Section: Migrating P Pubis: Eyelashes and Scalpmentioning
confidence: 99%
See 2 more Smart Citations
“…The eyelid needs careful examination with good lighting, possibly requiring a slit lamp. Case reports have suggested various treatments, including tea‐tree oil, physostigmine, pilocarpine and fluorescein ophthalmic drops; these seem to be used for occlusive purposes with no obvious pediculicidal properties 9,18,28,29 . Cryotherapy, argon lasers or botox have been used in difficult cases to structurally damage the lice and facilitate removal 18–19,29 .…”
Section: Migrating P Pubis: Eyelashes and Scalpmentioning
confidence: 99%
“…However, these are invasive and expensive options. Recommended treatment options are summarized in Table 2 6,13,14,16,17,28,29 …”
Section: Migrating P Pubis: Eyelashes and Scalpmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs that stick to the hairs are called nits. Female pubic lice leave their eggs after providing nutrients to them (Altınsoy et al, 2018;Roberts and Janovy, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In inguinal lice, the infectious stage is observed in adults and can be transmitted from person to person, mostly through sexual contact, less through clothing, contaminated toilets, and beds (Anderson and Chaney 2009). In different studies, it has been shown that pubic lice can be transmitted between family members, not only between spouses but also especially young children who are in close contact with their parents, by settling on the eyelids and clinically leading to pitriasis palpebrarum (Veraldi et al, 2009;Altınsoy et al, 2018). In the study, the wife and children of the clinical case that we evaluated did not have a history of the disease.…”
Section: The Parasitic Infestation Of Pubic Licementioning
confidence: 99%